Affective Contagion: How Attitudes Expressed by Others Influence Our Perception of Actions - Di Cesare, Giuseppe; Pelosi, Annalisa; Aresta, Silvia Maria; Lombardi, Giada; Sciutti, Alessandra (Frontiers in Human Neuroscience, 2021)
Vitality forms represent a fundamental aspect of social interactions, characterizing how actions are performed and how words are pronounced, on the basis of the agent’s attitude. The same action, such as a handshake, has a different impact on the receiver when it is performed kindly or vigorously, and the same happens with a gentle or rude tone of voice. In the present study, we carried out two experiments which aimed to investigate whether and how vocal requests conveying different vitality forms can influence the perception of goal-directed actions and to measure the duration of this effect over time. More specifically, participants listened to an actor voice pronouncing “give me” in a rude or gentle way, and then they were asked to observe the initial part of a rude or gentle passing action, continue it mentally and estimate the time of its completion. Results showed that the perception of different vitality forms expressed by vocal requests influenced the estimation of action duration. Moreover, we found that this effect was limited to a certain time interval (800ms), after which it started to decay.